Populations of phytonematodes associated to the vigor of plantain plants - González-García, Hebandreyna (2021)
Introduction. The biotic fraction of the soil is the essential component in ecological processes and can influence agricultural productivity of crops. Objective. To Identify the population of phytonematodes associated with plantain plants vigor in the southern zone of lake Maracaibo, Venezuela. Materials and methods. Eight 2-hectare batches of plantain plants (Musa AAB cv. Hartón), located in the south of lake Maracaibo, were selected and divided into two 1-hectare areas or lots, during October and December of the year 2018. The designation of the lots by vigor (HV= high vigor and BV= low vigor) was made based on the parameters of the number of hands per cluster, circumference of the mother plant, and the height of the son of succession, in twenty plants close to harvest, for each one. The soil sample was collected at a depth of 15 cm on three newly flowered plants per lot and for the roots a microcalicata was made per plant up to 30 cm deep. For the nematological extraction in the soil, the oostenbrink levigation method was used with a Baermann funnel and the blending method was used as a root. Subsequently, the specimens found were quantified by gender. Results. A population more significant (p<0,05) than in the root (2670 individuals) was found in the soil (14 140 individuals). No statistical difference between AV (395) and BV (305) was observed when comparing the total population by vigor. Twelve taxonomic genera were determined in the root and soil samples. The most prevalent specimens in AV were Helicotylenchus multicinctus and Radopholus similis and in the BV lots it was Pratylenchus sp. Conclusion. A high diversity of nematofauna present in both soils and roots of the crop was observed.